A randomized controlled pilot study feasibility of a tablet‐based guided audio‐visual relaxation intervention for reducing stress and pain in adults with sickle cell disease. (15th January 2016) - Ezenwa, Miriam O.; Yao, Yingwei; Engeland, Christopher G.; Molokie, Robert E.; Wang, Zaijie Jim; Suarez, Marie L.; Wilkie, Diana J.
Abstract: Aim: To test feasibility of a guided audio‐visual relaxation intervention protocol for reducing stress and pain in adults with sickle cell disease. Background: Sickle cell pain is inadequately controlled using opioids, necessitating further intervention such as guided relaxation to reduce stress and pain. Design: Attention‐control, randomized clinical feasibility pilot study with repeated measures. Methods: Randomized to guided relaxation or control groups, all patients recruited between 2013–2014 during clinical visits, completed stress and pain measures via a Galaxy Internet‐enabled Android tablet at the Baseline visit (pre/post intervention), 2‐week posttest visit and also daily at home between the two visits. Experimental group patients were asked to use a guided relaxation intervention at the Baseline visit and at least once daily for 2 weeks. Control group patients engaged in a recorded sickle cell discussion at the Baseline visit. Data were analysed using linear regression with bootstrapping. Results: At baseline, 27/28 of consented patients completed the study protocol. Group comparison showed that guided relaxation significantly reduced current stress and pain. At the 2‐week posttest, 24/27 of patients completed the study, all of whom reported liking the study. Patients completed tablet‐based measures on 71% of study days (69% in control group, 72% in experiment group). At the 2‐week posttest, the experimental group had significantly lower composite pain index scores, but the two groups did not differ significantly on stress intensity. Conclusion: This study protocol appears feasible. The tablet‐based guided relaxation intervention shows promise for reducing sickle cell pain and warrants a larger efficacy trial. Trial registration: The ClinicalTrials.gov Identifier is: NCT02501447.